CONTRIBUTIONS FROM THE CAPABILITIES APPROACH TO THE HUMAN RIGHTS PRACTICE - Braga Navarro, Gabriela Cristina [UNESP] (Univ Estado Rio Janeiro, 2020)
The article analyses the contributions offered from the capabilities approach to the human rights theory. The capabilities approach is a theory developed by Martha Nussbaum, US-American philosopher, that analyses the basic capabilities (alternative combinations of functionings that a person have the possibility to achieve) necessary for achieving a life with dignity, with special focus on gender vulnerability. The article demonstrates that Nussbaum's theory contributes greatly for the practice of human rights, by offering a list of specific capabilities that should be guaranteed to every human being by the State, with particular concern for vulnerable groups such as women, children and elderly. Even though the theory presents indisputable contributions, criticism is also presented, based upon mostly its essentialist point of view. In order to achieve the proposed objective, the methodology applied was bibliographical review.
Keywords: Capabilities approach; human rights; valuable functionings; Martha Nussbaum; social justice